Emerging Quest for Cannabis Policy Reforms: Growing Voices from Men and the Younger Population at the Grassroots in Kenya - Olungah, Charles Owuor (Advances in Social Sciences Research Journal, 2023)
“Meru Couple jailed for Life for Trafficking Kshs 3 million Marijuana” (Daily Nation 30th September 2021). “Man sentenced to Life Imprisonment for Trafficking bhang worth Kshs 23,250” (The Standard of 16th May 2018). “Why Small Amount of Bhang Earned Woman 30-year Sentence” (Kenya News of 23rd May 2019).